Antioxidative action of royal jelly in the yeast cell - Jamnik, Polona; Goranovič, Dušan; Raspor, Peter (Experimental gerontology, 2007)
Royal jelly is a bee product, secreted from the hypopharingeal and mandibular glands of worker bees. There are many reports on pharmacological activities of royal jelly in experimental animals, but there are few about its antioxidative properties connected to aging. The aim of the work was to investigate the antioxidative action of royal jelly in the cell of the yeast Saccharomyces cerevisiae as a model organism. Yeast was cultivated in YEPD medium enriched with different concentrations of royal jelly like 1, 2 and 5 g/L. Yeast growth was monitored by measuring optical density. At different time points cell energy metabolic activity was measured using the cell energy metabolism indicator resazurin, and 2′,7′-dichlorofluorescein was applied to estimate intracellular oxidation. Additionally, protein profile of cell extract was analyzed by 2-D electrophoresis. Results showed that royal jelly decreased intracellular oxidation in a dose dependent manner. Additionally it affected growth and cell energy metabolic activity in a growth phase dependent manner. Protein profile analysis showed that royal jelly in the cell does not act only as a scavenger of reactive oxygen species, but it also affects protein expression. Differentially expressed proteins were identified.